Water wave measurement from stereo images of specular reflections - Kiefhaber, Daniel; Caulliez, Guillemette; Zappa, Christopher J.; Schaper, Julia; Jähne, Bernd (Measurement science and technology, 2015)
A new optical instrument for the study of ocean waves, the Reflective Stereo Slope Gauge, has been developed. Its purpose is to measure ocean wave field parameters that are crucial to the air-sea exchange of momentum, heat and gases. The instrument combines a statistical wave slope measurement method similar to Cox and Munk’s sun glitter technique with a dedicated stereo camera and associated illumination setup for direct wave height measurements. The instrument output was validated under controlled conditions in a wind-wave facility.
Gesehen am 01.07.2020